Efficiency of Microwave Ablation for Cortisol-Producing Adrenal Adenomas: Case Series and a Literature Review - Krasavceva, Alicija; Jarašūnas, Juozas; Jocius, Donatas; Laukienė, Romena; Visockienė, Žydrūnė; Beiša, Virgilijus (Acta medica Lituanica, 2025)
Background: Adrenal adenomas, often discovered during imaging studies for unrelated conditions, pose diagnostic and therapeutic challenges due to their varying presentations and potential for hormone secretion. While surgical management remains the standard approach for hormonally active adrenal tumors, percutaneous ablation techniques – such as microwave ablation – have emerged as promising alternatives, particularly for patients who are not candidates for surgery.Materials and methods: This report presents a series of clinical cases in which percutaneous microwave ablation was used as an alternative to adrenalectomy. The study focuses on patients with cortisol-producing adrenal adenomas and explores the effectiveness of this minimally invasive procedure in achieving hormonal control and symptom relief.Results: Microwave ablation was successfully performed in all cases without major complications. Clinical follow-up demonstrated improvement in cortisol levels and relief of symptoms related to hypercortisolism. The procedure was well tolerated, offering an alternative therapeutic option for patients unsuitable for adrenalectomy.Conclusions: Percutaneous microwave ablation may serve as a safe and effective treatment option for cortisol-secreting adrenal adenomas in patients with Mild Autonomous Cortisol Secretion and ACTH-independent Cushing Syndrome who are not candidates for surgery. This approach may provide significant symptom relief and hormonal control with minimal invasiveness.